Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science

Consideration of the manufacturing history of sheet metal components for the adaptation of a clinching process - Heyser, Per; Wiesenmayer, S; Frey, P; Nehls, T; Scharr, C; Flügge, W; Merklein, M; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
The process chain for the manufacturing of sheet metal components in mass production includes various cutting and forming operations, which influence the resulting properties of the parts and therefore subsequent manufacturing steps, such as clamping and joining. It is shown that clamping of the components leads to superimposed residual stresses and geometry changes. Therefore, the part properties differ from the initial state of the semifinished products, which has to be considered in the design of clinched joints. This paper presents an approach for coupled determination of the properties of semifinished and finished parts during deep drawing and clamping as well as their effects on the joint quality during clinching. One method for the effective and efficient determination of the properties of semifinished products and components during production is using process data from the preceding manufacturing processes, which is concretely presented in this work. In addition to the interconnection of the entire production chain, it is necessary to define relevant process data for each individual manufacturing step and to correlate the data with the material properties reliably. Therefore, the cross-process interactions of different steps of the process chain for the manufacturing of sheet metal components and the effect of process variations on subsequent manufacturing steps are investigated. Consequently, the boundary conditions for a mechanical joining process based on data from preceding process steps can be predicted.
Keywords: Mechanical Engineering; General Materials Science

Metamodellbasierte Prozesskette - Umformen-Schneiden-Spannen-Fügen - Heyser, Per; Meschut, Gerson; Nehls, Thomas; Scharr, Christian; Froitzheim, Pascal; Flügge, Wilko; Wiesenmayer, Sebastian; Merklein, Marion (Pressen, Systeme, Prozesse der Zukunft Effizienz + Digitalisierung)

Konzeption einer adaptiven Prozesskette für das mechanische Fügen - Meschut, Gerson; Heyser, Per; Merklein, Marion; Wiesenmayer, Sebastian; Flügge, Wilko; Scharr, Christian; Nehls, Thomas

Smart process chain – data analysis in sheet metal processing for joinability prediction - Heyser, Per; Wiesenmayer, Sebastian; Nehls, Thomas; Scharr, Christian; Flügge, Wilko; Merklein, Marion; Meschut, Gerson (SMART PRODUCTION 2022: DIGITALIZING AUTOMOTIVE MANUFACTURING)

Fiber response to pin penetration in dry woven fabric using numerical analysis - Droß, M.; Heyser, Per; Meschut, Gerson; Hürkamp, A.; Dröder, K. (Journal of Advanced Joining Processes)

Increased load bearing capacity of mechanically joined FRP/metal joints using a pin structured auxiliary joining element - Heyser, Per; Sartisson, Vadim; Meschut, Gerson; Droß, Marcel; Dröder, Klaus (Materials Testing)

Prozesskettenbegleitende Vorgehensweise beim Mechanischen Fügen - Heyser, Per; Scharr, Christian; Nehls, Thomas; Wiesenmayer, Sebastian; Flügge, Wilko; Meschut, Gerson (4. Workshop Digitalisierung)

Berücksichtigung der Herstellungshistorie von Blechbauteilen beim Fügen durch Umformen - Wiesenmayer, Sebastian; Heyser, Per; Nehls, Thomas; Frey, Philipp; Flügge, Wilko; Meschut, Gerson; Merklein, Marion (Werkstattstechnik Online)

Increasing the strength of mechanically joined connections of metal and fiber-reinforced plastics using a structured auxiliary joining element - Dross, Marcel; Heyser, Per; Huerkamp, André; Beuscher, Jan; Dröder, Klaus; Meschut, Gerson (ICCM22 Proceedings)

Auxiliary joining element with integrated pin structures for mechanical joining of fiber-reinforced plastic/metal combinations - Heyser, Per; Meschut, Gerson; Dross, Marcel; Dröder, Klaus (ICCM22 Proceedings)

Steigerung der Tragfähigkeit mechanisch gefügter FKV-Metall-Verbindungen durch den Einsatz eines Pin-strukturierten Hilfsfügeteils - Heyser, Per; Meschut, Gerson; Dross, Marcel; Dröder, Klaus (9. Fügetechnisches Gemeinschaftskolloquium)

Entwicklung eines Fügeelements mit integriertem strukturierten Formabschnitt - Heyser, Per; Meschut, Gerson; Dross, Marcel; Dröder, Klaus